Evaluation of hydrophilic surface osseointegration in low-density bone: Preclinical study in rabbits - Pinto, Gustavo Da Col Santos [UNESP]; Dos Reis, Isadora Aparecida Ribeiro; Leocádio, Amanda De Carvalho Silva [UNESP]; Silva, Matusalem; Faeda, Rafael Silveira; De Oliveira, Guilherme José Pimentel Lopes; Marcantonio, Elcio [UNESP] (FapUNIFESP (SciELO), 2023)
The aim of this study was to evaluate the osseointegration of a hydrophilic surface (blasting + acid etching + immersion in isotonic solution) in comparison with that of a control surface (blasting + acid etching) using an experimental model of low-density bone. To perform the study, 24 rabbits were submitted to the installation of 4 implants in the iliac bone bilaterally: 2 implants with a control surface and 2 implants with a hydrophilic surface. The rabbits were euthanized at 2, 4, and 8 weeks after implant installation. After euthanasia, one implant from each surface was used to perform the removal torque analysis, and the other implant was used for the execution of nondecalcified histological sections and evaluation of the bone implant contact (°/o BIC) as well as the fraction of bone tissue area between the implant threads (%BBT). The implants with a hydrophilic surface presented higher %BIC (42.92 ± 2.850/0 vs. 29.49 ± 10.27Q/6) and %BBT (34.32 ± 8.52% vs. 23.20 ± 6.75%) (p < 0.05) in the 2-week period. Furthermore, the hydrophilic surface presented higher removal torque in the 8-week period (76.13 ± 16.00 Ncm2 vs. 52.77 ± 13.49 Ncm2) (p<0.05). Implants with a hydrophilic surface exhibited acceleration in the process of osseointegration, culminating in greater secondary stability in low-density bone than in implants with a control surface.
Keywords: Bone-implant interface; Dental implants; Osseointegration